Complement Component C3 Participates in Early Stages of Niemann–Pick C Mouse Liver Damage - Andrés D. Klein; Javier González de la Vega; Silvana Zanlungo (My University, 2020)
Niemann–Pick type C (NPC), a lysosomal storage disorder, is mainly caused by mutations in the NPC1 gene. Niemann–Pick type C patients and mice show intracellular cholesterol accumulation leading to hepatic failure with increased inflammatory response. The complement cascade, which belongs to the innate immunity response, recognizes danger signals from injured tissues. We aimed to determine whether there is activation of the complement system in the liver of the NPC mouse and to assess the relationship between C3 activation, a final component of the pathway, and NPC liver pathology. Niemann–Pick type C mice showed high levels of C3 staining in the liver which unexpectedly decreased with aging. Using an inducible NPC1 hepatocyte rescue mouse model, we restored NPC1 expression for a short time in young mice. We found C3 positive cells only in non-rescued cells, suggesting that C3 activation in NPC cells is reversible. Then, we studied the effect of C3 ablation on NPC liver damage at two postnatal time points, P56 and P72. Deletion of C3 reduced the presence of hepatic CD68-positive cells at postnatal day 56 and prevented the increase of transaminase levels in the blood of NPC mice. These positive effects were abrogated at P72, indicating that the complement cascade participates only during the early stages of liver damage in NPC mice, and that its inhibition may serve as a new potential therapeutic strategy for the disease.
Keywords: cholesterol; complement cascade; foam cells; liver damage; lysosomal storage diseases; niemann–pick type c disease; alanine aminotransferase; aminotransferase; aspartate aminotransferase; cd68 antigen; cholesterol; complement component c3; doxycycline; filipin; tetracycline; animal cell; animal experiment; animal model; animal tissue; article; cell structure; complement activation; controlled study; foam cell; immunohistochemistry; liver cell; liver histology; liver injury; mouse; niemann pick disease; nonhuman; protein expression; staining; tissue section